INTEGRATING ONLINE TOOLS FOR ENHANCED ENGLISH GRAMMAR INSTRUCTION (International Conference on Modern Science and Scientific Studies, 2025)
The landscape of education has undergone a profound transformation, shaped dramatically by the pervasive influence of digital technology. Today’s learners, often described as digital natives, navigate a world saturated with online resources, interactive platforms, and instant connectivity. Against this backdrop, the traditional methods of teaching English grammar—often reliant on textbooks, blackboard explanations, and repetitive drills—are increasingly proving insufficient to capture student attention and foster deep, lasting understanding. These conventional approaches, while holding historical significance, frequently fail to prepare learners for the dynamic, real-world linguistic demands they will encounter. This article delves into the transformative potential of integrating online tools into English grammar instruction, moving beyond static methodologies to cultivate dynamic, engaging, and highly personalized learning experiences.